«Under His Eye»: reflections on the Role of Technology on Women’s Body After the US Supreme Court Judgment in the Dobbs Case (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This short piece is aimed at showing that the role of technology with regard to women’s access to abortion is twofold: on the one hand, it is an empowering instrument, because through telemedicine women can overcome the limits of restrictive domestic laws; on the other hand, it might constitute a means to control women through tracking data from visitors to abortion clinics. The analysis is based on international human rights law, considering the specific situation in the US, but also taking into account the role of European NGOs in the provision of services through telemedicine.